Application of cell culture technology and genetic engineering for production of future foods and crop improvement to strengthen food security - Rachma Wikandari (Taylor & Francis Group, 2021)
The growing population and the climate changes put a pressure on food production globally, therefore a fundamental transformation of food production is required. One approach to accelerate food production is application of modern biotechnology such as cell culture, marker assisted selection, and genetic engineering. Cell culture technology reduce the usage of arable land, while marker assisted selection increases the genetic gain of crop breeding and genetic engineering enable to introduce a desired traits to crop. The cell culture technology has resulted in development of cultured meat, fungal biomass food (mycoprotein), and bioactive compounds from plant cell culture. Except cultured meat which recently begin to penetrate the market, the other products have been in the market for years. The marker assisted selection and genetic engineering has contributed significantly to increase the resiliency against emerging pests and abiotic stresses. This review addresses diverse techniques of cell culture technology as well as advanced genetic engineering technology CRISPR Cas-9 and its application for crop improvement. The pros and cons of different techniques as well as the challenges and future perspective of application of modern biotechnology for strengthening food security are also discussed.